The influence of group counseling services on increasing the self-confidence of broken home students at SMK Negeri 2 Rantau Utara - Selly Selly; Karina Ulfa Syaimi B (Sean Institute, 2024)
The family is the smallest unit of society consisting of father, mother and children who live under one roof, namely the house. There are many problems in the household, one of which is a broken home. Broken Home here is defined as the destruction of a household resulting in the divorce of husband and wife. In this sense, it shows clearly the condition of the family. Broken Home is a family that is not in order, of course it will have a negative effect on children who are at school, for example low enthusiasm for learning, low self-confidence and having few friends . They will feel frustrated with the situation of their parents who no longer live together. This research was carried out at SMK N 2 Rantau Utara. The aim of this research is to see whether or not there is an influence of group counseling services on students at SMK Negeri 2 Rantau Utara who experience broken homes. Data collection techniques use interviews, observation and documentation. Next, the data was analyzed qualitatively using 3 models, namely instrument validation tests to test product moment correlation, alpha formula to test instrument reliability, SPSS for window reliance 25 to view interview experiment data. The results of the research show that group counseling services using discussion techniques can have an effect on increasing self-confidence in students in class X DPIB 1 and X DPIB 2 at SMK Negeri 2 Rantau Utara. This can be clearly seen in the difference in self-confidence scores between subjects before being given counseling services using discussion techniques and after being given group counseling services. Thus, it can be concluded that the implementation of counseling has a clear objective in providing services, namely to enable students to increase their self-confidence.